A retrospective study on factors affecting length of stay in Hospital Universiti Sains Malaysia (HUSM) for dengue fever in adults patients : a five years review - Rani, Rahaizah (2016)
INTRODUCTION Dengue fever is caused by dengue virus (DEN), a flaviviridae and transmitted to human by mosquito vector, usually Aedes aegypti. Basic clinical features recorded in adult dengue patients on admission to the emergency room are fever, headache, myalgia, back pain, arthralgia, vomiting, rashes, lymphocytopenia and thrombocytopenia. Dengue fever is a common presentation in emergency and trauma department in Malaysia and results in large number of hospital admission. However, there is no published data found regarding factors affecting length of stay in dengue fever especially in our country. Therefore this study was done to describe the sociodemographic, clinical profiles, outcome, length of stay and associated factors affecting length of stay. OBJECTIVES 1. To describe the statistic of dengue patients and their demographic characteristics, clinical profiles and its outcome. 2. To determine mean length of stay in dengue patients. 3. To determine the association between clinical profiles of dengue patients with dengue serology 4. To determine the association between socio-demographic characteristics and clinical profiles of dengue patients with length of stay 5. To identify associated factors in demographic characteristics and clinical profile of dengue patients affecting length of stay METHODOLOGY A retrospective cross-sectional study was done from January 2007 to December 2011 on eligible patients suspected or confirmed dengue fever in HUSM. Patients’ medical records were traced from the record office, reviewed and the data were recorded using the data collection form. The socio-demographic characteristics, clinical profiles, outcome, length of stay, factors affecting length of stay and other parameters were analyzed using SPSS version 20.0. RESULTS 1. .The mean age of the patients in this study was 33.95 (6.614) years old. 66.1% of patients were male, and the most common co-morbid diseases was hypertension (9.8%). All patients presented with fever, 95.3% had body ache and 58.8% had IgM positive. The mean length of stay was 3.98 (2.46) days. Symptom of rashes, diastolic blood pressure, shock index and haematocrit level were found to have significant association with dengue serology result. Patients with diabetes mellitus, hyperlipidaemia, symptom of rashes, pulse rate at emergency department, shock index in the ward, ascites and dengue serology result had significant association with length of stay. Patients with co-morbid diabetes mellitus, background of hyperlipidaemia, underlying bronchial asthma, symptom of fever, diastolic blood pressure reading at emergency department, temperature at emergency department and ascites were the significant associated factors affecting length of stay. CONCLUSION We concluded that socio-demographic as well as clinical profiles were the associated factors affecting length of stay in dengue fever. Diabetes mellitus, hyperlipidaemia, bronchial asthma, symptom of fever, diastolic blood pressure at emergency department, temperature at emergency department, and ascites were the significant associated factors affecting length of stay in dengue patients.